2011
DOI: 10.1007/s12011-011-9208-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Zinc Levels Associated with Giardiasis and Dietary Zinc Intake in Mice

Abstract: The association of giardiasis with the malabsorption of zinc remains controversial. This study investigated changes in serum zinc levels in Giardia-infected mice subjected to different dietary zinc regimens. Thirty-five mice (strain C(3)H/H(e)J) were randomly categorized into two groups. The first group was inoculated with 5 × 10(6) Giardia trophozoites (n = 18), and the second group remained Giardia free (n = 17). Each group (Giardia infected and Giardia free) was randomly classified into three subgroups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…In our study, Giardia -infected mice in all dietary groups had lower serum zinc levels than non-infected mice after 30 days p.i. This is in agreement with other authors whose studies showed that giardiasis may be a risk factor for zinc deficiency in mice regardless of the dietary intake [35]. However, the “extra” zinc provided by the ZnH and ZnS diets helped maintaining the zinc levels near those of the ZnA Giardia -free mice.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, Giardia -infected mice in all dietary groups had lower serum zinc levels than non-infected mice after 30 days p.i. This is in agreement with other authors whose studies showed that giardiasis may be a risk factor for zinc deficiency in mice regardless of the dietary intake [35]. However, the “extra” zinc provided by the ZnH and ZnS diets helped maintaining the zinc levels near those of the ZnA Giardia -free mice.…”
Section: Discussionsupporting
confidence: 93%
“…Trophozoites on each 1 mm² square (4 in total) were microscopically counted at 40x magnification (Microscope Olympus, CKX41, Center Valley, PA, USA). The total number of trophozoites per mL was calculated as follows: (Number of trophozoites/4 squares) × (500/100) × 10000 [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Although anti-microbial effects of zinc have been reported for several pathogenic species, including EPEC, ETEC, and STEC, [21][22][23][24][25] Therefore, we sought to investigate whether zinc has a potential role in EAEC-host cell interaction at concentrations similar to physiological serum and intestinal lumen levels (0.01-0.05 mM). 26,27 The objectives of this study were to elucidate the effects of zinc on important properties of a strain of EAEC (042) associated with human disease, 28 as it interacts with intestinal epithelium, and to begin to identify specific mechanisms in vitro responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%